PROJECT BASED LEARNING FOR CREATING THE 21ST CENTURY ENGINEER - Julia N. Ziyatdinova; Phillip Albert Sanger (Moscow Polytechnic University, 2016)
Industry throughout the world demands engineering graduates that are better prepared to support their organizations. Project (or problem) based learning (PBL) approach gives engineering students an opportunity to learn by doing and apply their training to realworld problems. Different styles of implementing PBL are described, and a special attention is given to one of the themes of PBL, gradual transition from solving close ended problems to addressing real world open ended problems. The ultimate project experience is described in a global international project which explores not only the technical challenges of an open project but also the challenges of working collaboratively with engineering students from different cultures.